All‐Optical Switching Based on Sub‐Bandgap Photoactivation of Charge Trapping in Metal Halide Perovskites. Issue 13 (21st February 2023) - Wan, Sushu; Li, Ke; Zou, Meijun; Hong, Daocheng; Xie, Mingcai; Tan, Hairen; Scheblykin, Ivan G.; Tian, Yuxi
Abstract: Controllable optical properties are crucial for the application of light‐emitting materials in optical devices. In this work, controllable photoluminescence in metal halide perovskite crystals is realized via photoactivation of their defects. It is found that under continuous excitation, the photoluminescence intensity of a CH3 NH3 PbBr3 crystal can be fully controlled by sub‐bandgap energy photon illumination. Such optically controllable emission behavior is rather general as it is observed also in CsPbBr3 and other perovskite materials. The switching mechanism is assigned to reversible light‐induced activation/deactivation of nonradiative recombination centers, the presence of which relates to an excess of Pb during perovskite synthesis. Given the success of perovskites in photovoltaics and optoelectronics, it is believed that the discovery of green luminescence controlled by red illumination will extend the application scope of perovskites toward optical devices and intelligent control. Abstract : Photoluminescence (PL) of perovskite can be switched by other light with sub‐bandgap photon energy in a broad spectral range with high stability. This effect is controlled by photosensitive defects, in which concentration is modified by the crystal stoichiometry. This finding indicates a new application area of metal halide perovskites in optical switches, transistors, and memory.